Bioenergy crops grown for hyperaccumulation of phosphorous in the Delmarva Peninsula and their biofuels potential. (1st March 2015) - Boateng, Akwasi A.; Serapiglia, Michelle J.; Mullen, Charles A.; Dien, Bruce S.; Hashem, Fawzy M.; Dadson, Robert B.
Abstract: Herbaceous bioenergy crops, including sorghum, switchgrass, and miscanthus, were evaluated for their potential as phytoremediators for the uptake of phosphorus in the Delmarva Peninsula and their subsequent conversion to biofuel intermediates (bio-oil) by fast pyrolysis using pyrolysis-gas chromatography/mass spectroscopy. Four cultivars of sorghum, five cultivars of switchgrass and one miscanthus ( Miscanthus  ×  giganteus ) were grown in soils with two different levels of poultry manure (PM) applications. Little variation was seen in phosphorus uptake in the two different soils indicating that the levels of available phosphorus in the soil already saturated the uptake ability of the plants. However, all plants regardless of trial took up more phosphorus than that measured for the non- PM treated control. Sorghum accumulated greater levels of nutrients including phosphorus and potassium compared to switchgrass and miscanthus. The levels of these nutrients in the biomass did not have an effect on carbohydrate contents. However, the potential yield and composition of bio-oil from fast pyrolysis were affected by both agronomics and differences in mineral concentrations. Highlights: Sorghum accumulated more P and K then switchgrass or Miscanthus . Accumulation of these nutrients did not impact cell wall polysaccharide content. More pyrolysis oil was produced from biomass grown on the high-poultry manure site. Bio-oil from sorghum had lower oxygenates and hence improved stability.